Capturing the motion of molecular nanomaterials encapsulated within carbon nanotubes with ultrahigh temporal resolution. - Warner, J; Ito, Y; Rümmeli, M; Büchner, B; Shinohara, H; Briggs, G (2009)
We use in situ low-voltage aberration corrected high resolution transmission electron microscopy with a temporal resolution of 80 ms to track the motional dynamics of nanostructures encapsulated within carbon nanotubes. Two different nanostructures are examined and both are produced by electron beam irradiation of peapods containing La@C(82) metallofullerenes. The first novel nanostructure consists of a LaC(2) metal cluster attached to carbon nanotube inside a nanotube host. It exhibits repeated nanopiston-like behavior over a 5 min duration, driven by energy supplied by electron beam irradiation. Interaction of the metal cluster with the nanotube host is also examined, revealing that the metal cluster can open up the nanotube sidewall, exit, and then seal the hole in the wall back up with carbon from the surrounding region. Finally, the intrinsic motional dynamics of an isolated single fullerene within a SWNT is captured and we report velocities up to 112 nm/s.